Randomized Placebo‐Controlled Trial of Intravenous Immunoglobulin in Autoimmune LGI1/CASPR2 Epilepsy. Issue 2 (14th December 2019) - Dubey, Divyanshu; Britton, Jeffrey; McKeon, Andrew; Gadoth, Avi; Zekeridou, Anastasia; Lopez Chiriboga, Sebastian A.; Devine, Michelle; Cerhan, Jane H.; Dunlay, Katie; Sagen, Jessica; Ramberger, Melanie; Waters, Patrick; et al.
Abstract : Objective: Drug‐resistant seizures are common in patients with leucine‐rich, glioma‐inactivated 1 (LGI1)‐IgG associated and contactin‐associated protein‐like 2 (CASPR2)‐IgG associated encephalitis. We performed the first randomized double‐blind placebo‐controlled trial to evaluate efficacy of intravenous immunoglobulin (IVIG) in reducing seizure frequency. Methods: Our enrollment goal was 30 LGI1/CASPR2‐IgG–seropositive adult patients with ≥2 seizures per week. Patients were randomized to receive IVIG (0.5g/kg day 1, 1g/kg day 2, 0.6g/kg weeks 3 and 5) or volume‐matched intravenous normal saline. Following the blinded phase, the nonresponders in the placebo group received IVIG. The primary clinical outcome was 50% reduction in seizure frequency from baseline to 5 weeks. Results: After enrollment of 17 patients (LGI1‐IgG, 14; CASPR2‐IgG, 3) over 34 months, the study was terminated due to slow enrollment. Six of 8 patients in the IVIG group were responders, compared to 2 of 9 in the placebo group ( p = 0.044, odds ratio = 10.5, 95% confidence interval = 1.1–98.9). For the LGI1‐IgG seropositive subgroup, 6 of 8 patients in the IVIG group were responders, compared to zero of 6 in the placebo group. Two LGI1‐IgG–seropositive patients receiving IVIG, but none receiving placebo, were seizure‐free at the end of the blinded phase. Four of the 6 patients entering the open‐label IVIG arm reported ≥50% reduction in seizure frequency. There were no correlations with LGI1/CASPR2‐IgG1–4 subclasses. Interpretation: Superiority of IVIG to placebo reached statistical significance for the primary endpoint for all patients and the subset with LGI1‐IgG. These results have to be interpreted with the caveat that the study did not reach its originally selected sample size. ANN NEUROL 2020;87:313–323